2013
DOI: 10.1002/nau.22387
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of videourodynamics using smart phone and free instant messaging software

Abstract: The qualities of videourodynamics under the attending physician's remote or direct monitoring were both appropriate. Based on the convenience of Internet, the popularity of smart phones and the intention to make the urologists use their time more efficiently, our study provides remote monitoring as an alternative way for performing videourodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We classified twelve (44%) of the included studies as "feasibility studies" (Table 3); [5][6][7][8][9][10][11][12][13][14][15][16][17] nine (33%) as "clinical studies" (Table 5); [18][19][20][21][22][23][24][25][26] and six articles (22%) as "clinical education" studies (Table 7). 6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment.…”
Section: Study Purposementioning
confidence: 99%
See 2 more Smart Citations
“…We classified twelve (44%) of the included studies as "feasibility studies" (Table 3); [5][6][7][8][9][10][11][12][13][14][15][16][17] nine (33%) as "clinical studies" (Table 5); [18][19][20][21][22][23][24][25][26] and six articles (22%) as "clinical education" studies (Table 7). 6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment.…”
Section: Study Purposementioning
confidence: 99%
“…6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment. 8,22,30 Five studies (19%) reported a pre-test / post-test design, 9,11,16,26,28 while three (11%) reported method-comparison studies. 14,20,24 Qualitative designs were …”
Section: Study Purposementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the accessibility of knowledge via the internet has triggered an increase in the enthusiasm of patients who try and understand their illness by accessing available data. Smartphones, which have features similar to computers and are carried by almost everyone, have been demonstrated to have potential as medical monitoring systems for patients 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Hospitals and medical schools now commonly use remote audio-and video-based technologies for instruction and training (3)(4)(5) , and many physicians provide video consultations through real-time online consultation platforms such as MDLi-veCare and SwiftMD (6) . Health care providers are even using digital real-time video technology platforms to deliver health care in rural and/or resource-limited areas (7)(8)(9)(10)(11)(12) and to remotely diagnose, monitor or treat medical conditions ranging from orthopaedic trauma to neurological disorders (1,10,(13)(14)(15)(16)(17)(18)(19)(20)(21) .…”
mentioning
confidence: 99%